Rapid contextual design a how-to guide to key techniques for user-centered design - Holtzblatt, Karen; Wendell, Jessamyn Burns; Wood, Shelley (San Francisco : Elsevier/Morgan Kaufmann, 2005)
Is it impossible to schedule enough time to include users in your design process? Is it difficult to incorporate elaborate user-centered design techniques into your own standard design practices? Do the resources needed seem overwhelming? This handbook introduces Rapid CD, a fast-paced, adaptive form of Contextual Design. Rapid CD is a hands-on guide for anyone who needs practical guidance on how to use the Contextual Design process and adapt it to tactical projects with tight timelines and resources. Rapid Contextual Design provides detailed suggestions on structuring the project and customer interviews, conducting interviews, and running interpretation sessions. The handbook walks you step-by-step through organizing the data so you can see your key issues, along with visioning new solutions, storyboarding to work out the details, and paper prototype interviewing to iterate the designall with as little as a two-person team with only a few weeks to spare! *Includes real project examples with actual customer data that illustrate how a CD project actually works. *Covers the entire scope of a project, from deciding on the number and type of interviews, to interview set up and analyzing collected data. Sample project schedules are also included for a variety of different types of projects. *Provides examples of how-to write affinity notes and affinity labels, build an affinity diagram, and step-by-step instructions for consolidating sequence models. *Shows how to use consolidated data to define a design within tight time frames with examples of visions, storyboards, and paper prototypes. *Introduces CDTools, the first application designed to support customer-centered design.
Chapter 1: Introduction -- Chapter 2: Planning Your Rapid CD Project -- Chapter 3: Planning Your Contextual Interviews -- Chapter 4: The Contextual Inquiry Interview -- Chapter 5: Contextual Interview Interpretation Session -- Chapter 6: Work Modeling -- Chapter 7: Building an Affinity Diagram -- Chapter 8: Consolidated Sequence Models -- Chapter 9: Using Contextual Data to Write Personas -- Chapter 10: Walking the Affinity and Consolidated Sequences -- Chapter 11: Visioning a New Way to Work -- Chapter 12: Storyboarding -- Chapter 13: Testing with Paper Prototypes -- Chapter 14: Paper Prototype Interviews -- Chapter 15: Rapid CD and Other Methodologies -- Chapter 16: Issues of Organizational Adoption -- Appendix 1: Supply Checklist -- Index.
Includes bibliographical references and index.
Keywords: System design; System analysis; Electronic books